Trigeminal neuralgia improvement following Transcutaneous Electrical Nerve Stimulation (TENS): a systematic review and meta-analysis - Yazan AlHabil; Khulood Al-Sayed; Ashraf Salameh (BMC Neurology)
Abstract Background Trigeminal neuralgia (TN) is a prevalent and debilitating craniofacial pain disorder characterized by severe, unilateral, shock-like pain. Standard treatments include anti-epileptic drugs and surgical interventions, but many patients experience limited relief or adverse effects. Non-invasive therapies, such as transcutaneous electrical nerve stimulation (TENS), have emerged as alternative options. This systematic review and meta-analysis aimed to evaluate the efficacy of TENS in managing primary trigeminal neuralgia. Methods A comprehensive search of PubMed, Cochrane Library, and Google Scholar was conducted, yielding 89 papers. Following selection criteria, five clinical trials involving 101 patients with primary TN and TENS treatment were included. Data on pain severity, TENS parameters, and outcomes were extracted. Statistical analysis was performed using RevMan software, with outcomes assessed using Visual Analogue Scale (VAS) scores before and after TENS treatment. Results Pre-treatment VAS scores averaged 8.75 ± 0.18, indicating severe pain. Post-treatment, the mean VAS score significantly decreased to 1.17 ± 0.55, demonstrating substantial pain relief. The meta-analysis revealed a mean difference of 7.49 (95% CI: 7.05 to 7.93) in VAS scores, with a p-value < 0.05, indicating statistically significant pain reduction. Heterogeneity among studies was moderate (I2 = 57%). Complications were infrequently reported, with one study noting paresthesia in a small number of patients. Conclusion TENS appears to be an effective and safe intervention for reducing pain in patients with primary trigeminal neuralgia. Despite variability in treatment protocols and follow-up periods, the overall evidence supports TENS as a viable option for managing TN pain. Future research should focus on standardizing TENS protocols and evaluating long-term efficacy and safety.